Evaluation of Autism Student Learning Program in Special Schools in North Sulawesi Province - Kalalo, Debie K.R.; Rawis, Joulanda A M; Lumapow, Harol R.; Lengkong, Jeffry Sony Junus; Kambey, Joseph Philip; Palilingan, Rolles N.; Umbase, Ruth; Tamboto, Hendry (JR Education, 2025)
This study was conducted to evaluate the learning program for students with autism spectrum disorders in Special Needs Schools (SLB) in North Sulawesi Province. The research context is based on the increasing number of children with autism, limited special education services, and the need for adaptive, individualized, and independence-oriented learning models. The research objectives include evaluating the learning program, identifying implementation barriers, and mapping supporting factors in the implementation of learning at the Hizkia Manado Special Needs School for Autism, Efatah Bitung Special Needs School, and Paulus Tomohon Special Needs School. The study used a descriptive qualitative approach through in-depth interviews, observations, and documentation analysis, and involved policymakers, principals, teachers, and parents. The results showed that the learning program has attempted to adhere to the principles of individualization through the IEP, the use of methods such as ABA, TEACCH, and PECS, and the inclusion of supportive therapy. However, implementation is still hampered by the limited number of teachers with special education competencies, the lack of autism-friendly infrastructure, unequal access to therapy services, and low parental involvement. On the other hand, policy support, cross-sector collaboration, and teacher and school commitment are significant supporting factors. The study concluded that improving the quality of learning requires strengthening human resources, developing learning infrastructure tailored to the needs of children with autism, and integrating education and health services. Consequently, local governments and schools need to develop holistic and sustainable service designs to ensure optimal academic, social, and independence development for students with autism.